The effects of specific drills on the flip turns of freestyle swimmers based on a kinesiology analysis - Wen, Y.; Peng, Y.; Zhao, F.; Zhen, K. (Journal of Human Kinetics, 2016)
This research aimed to define the key factors in freestyle flip turns via a kinesiology analysis to diagnose swimmers. Hence, specially designed drills were created to improve swimmers` flip-turn skills and assess the effects of training. Nine Chinese national modern pentathlon athletes ranging in age from 20 to 26 years with an average of 10 years of training experience were tested and trained in this study. The Kistler Performance Analysis System for Swimming was used for the pre- and post-test analyses. A kinesiology analysis of the data from the pre-test was used for the diagnosis and specific drills were adopted for 10 weeks, 3 times per week before the post-test. The comparison of the pre- and post-test performances was used to assess the effects of training. After 10 weeks of specific drill training for flip turns, participants` turning skills significantly improved. Speed in approaching, somersaulting, pushing-off and gliding all increased. The angles of the knees and hips as well as the force applied improved, which contributed to swimmers` increased speed. Since the skills needed for a flip turn are complex and not easily diagnosed via observation alone, this kinesiology analysis will make diagnosis objective and easy.